Penggunaan Alat Musik Tambua pada Acara Baralek di Hamparan Perak, Deli Serdang - Piere Steven Randall Sitepu; Rithaony Hutajulu; Vanesia Amelia Sebayang (Mahesa Research Center, 2026)
This research discusses the use of the Tambua musical instrument in the Baralek ceremony (Minangkabau traditional wedding) held in Hamparan Perak, Deli Serdang. The study focuses on the presentation form, function, and symbolic meaning of the Tambua music within the context of the ritual. The approach used is qualitative descriptive ethnomusicology, with data collection through observation, in-depth interviews, and documentation. The key informants are members of Sanggar Tuah Sakato Medan, who are actively preserving Minangkabau musical practices in the migrant area (perantauan). The results show that the Tambua is presented as an ensemble (along with Tansa, Gandang, Talempong, and Bansi), with a dynamic musical structure that is integrated with every stage of the Baralek procession. The Tambua plays a role as the accompaniment for the traditional procession, a builder of the sacred atmosphere, and a medium for symbolic communication. The embedded symbolic meanings reflect core Minangkabau cultural values, such as mutual cooperation (gotong royong) and kinship ties. It can be concluded that the use of the Tambua in Baralek not only functions as an artistic expression but is also a marker of cultural identity as well as a vital medium for the preservation of Minangkabau tradition in the migrant land.